التعرف على إشارات المرور باستخدام التعلم العميق - سلمي, منى; خزاني, مريم; غريبي, أشواق (Université of Eloued جامعة الوادي, 2026)
تعد حوادث المرور من أبرز المخاطر التي تهدد حياة اإلنسان، حيث تتسبب سنويا في عدد كبير من الوفيات على مستوى العالم. ومع االزدياد المستمر في أعداد المركبات وتعقيد حركة المرور، تت ازيد احتمالية وقوع هذه الحوادث بشكل ملحوظ. وفي هذا السياق، تبرز الحاجة إلى تطوير حلو ل تقنية فعالة تساهم في الحد من هذه المخاطر، ويعد إنشاء أنظمة ذكية ومتقدمة قادرة على التعرف على إشارات المرور والتفاعل معها بدقة عالية أحد أبرز هذه الحلول. مؤخرا، أظهرت الدراسات الحديثة دور تقنيات الذكاء االصطناعي، خصوصا التعلم اآللي والتعلم العميق في العديد من المجاالت، من بينها مجال السالمة المرورية. إذ تتيح هذه التقنيات بناء أنظمة قادرة على التعرف التلقائي على إشا ارت المرور واالستجابة لها بشكل فوري ودقيق. في هذا اإلطار، تم في هذه الدراسة تطوير نظام للتعرف على إشارات المرور باستخدام أحد نماذج التعلم العميق، وهو نموذج الشبكات العصبية االلتفافية - Networks Neural Convolutional( (CNN، حيث تم تدريب النموذج المقترح وتقييم أدائه باستخدام قاعدة بيانات واسعة تحتوي على مجموعة متنوعة من صور إشارات المرور. وقد أظهرت النتائج تفوق النموذج المقترح مقارنة بأساليب التعلم اآللي التقليدية التي جربناها من حيث الدقة والكفاءة. Traffic accidents are among the leading causes of fatalities worldwide, posing a significant threat to human life on a global scale. As vehicle density continues to rise and traffic systems grow increasingly complex, the risk of such accidents has escalated significantly. As a result, it has become es- sential to find effective solutions to reduce the risk of accidents. One of the most important solutions is the development of advanced and intelligent sys- tems to accurately recognize and interact with traffic signs. Recent studies have demonstrated the significant role of artificial intelli- gence technologies, particularly machine learning and deep learning, in en- hancing various fields, with a notable impact on traffic safety. This is achieved through the development of systems based on these technologies to recognize and interact with traffic signs, thereby significantly enhancing road safety. To this end, this study aims to develop a traffic sign recognition system based on a deep learning model, Convolutional Neural Networks (CNNs). The model was trained and evaluated using a large dataset of traffic sign images. The results demonstrated that the proposed model outperformed traditional machine learning methods. Keywords: Traffic signs, image processing, deep learning, artificial neural networks, machine learning, artificial intelligence, traffic sign recognition.
مذكرة تخرج ليسانس اعلام آلي
Keywords: الإشارات المرور، معالجة الصور، التعلم العميق، الشبكات العصبية االصطناعية، التعلم اآللي، الذكاء االصطناعي، التعرف على إشارات المرور; Keywords: Traffic signs; image processing; deep learning; artificial neural networks; machine learning; artificial intelligence; traffic sign recognition.